A bioinspired silica nanocomposite for enhanced multidrug-resistant bacteria treatment and wash-free imaging. Issue 6 (1st March 2023) - Liu, Xiaokun; Zhang, Zhiying; Tomczak, Nikodem; Yang, Cong; Li, Chengjun; Liu, Rongrong; Yan, Bing
Abstract : A bioinspired silica nanocomposite demonstrates potent antibacterial activity and real-time imaging capability against multidrug-resistant bacteria. Abstract : Bacterial infections have posed significant threats to public health due to the emergence of antibiotic resistance. In this work, a novel antibacterial composite nanomaterial based on spiky mesoporous silica spheres loaded with poly(ionic liquid)s and aggregation-induced emission luminogens (AIEgens) was designed for efficient multidrug-resistant (MDR) bacteria treatment and imaging. The nanocomposite exhibited excellent and long-term antibacterial activity towards both Gram-negative and Gram-positive bacteria. Meanwhile, fluorescent AIEgens facilitate real-time bacterial imaging. Our study provides a multifunctional platform and a promising alternative to antibiotics for combating pathogenic MDR bacteria.